2007
DOI: 10.1109/tpwrs.2007.908471
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Agent Systems for Power Engineering Applications—Part I: Concepts, Approaches, and Technical Challenges

Abstract: This is the first part of a two-part paper that has arisen from the work of the IEEE Power Engineering Society's Multi-Agent Systems (MAS) Working Group.Part I of this paper examines the potential value of MAS technology to the power industry. In terms of contribution, it describes fundamental concepts and approaches within the field of multiagent systems that are appropriate to power engineering applications. As well as presenting a comprehensive review of the meaningful power engineering applications for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
390
0
15

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 941 publications
(424 citation statements)
references
References 58 publications
1
390
0
15
Order By: Relevance
“…This step is modeled by the optimization problem (10). The producer procures and activates flexibility services based on the solution of problem (11).…”
Section: Producer and Retailermentioning
confidence: 99%
See 1 more Smart Citation
“…This step is modeled by the optimization problem (10). The producer procures and activates flexibility services based on the solution of problem (11).…”
Section: Producer and Retailermentioning
confidence: 99%
“…Agent-based modeling has been extensively used in the literature to model electric systems [10][11][12][13]. The OPTI-MATE open platform is an example of an agent-based tool used in power systems.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages (e.g., scalability, autonomy and intelligence) are illustrated through a case study describing a SCADA system for electricity transportation management. In [6,7] the authors focus on the application of MAS to power engineering, where problems are formalized, technologies are discussed, and several implementation issues are addressed. In [10] it is reported that MAS technologies outperform classical technologies in the protection of power distribution systems.…”
Section: Related Workmentioning
confidence: 99%
“…BDI agents have been used to develop SCADA systems by treating system components as autonomous agents, to provide better scalability, autonomy and intelligence [6,7,2]. Each agent's beliefs (knowledge about the environment), desires (goals), and intentions (commitments to act) are explicitly represented.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews show that multi-agent systems research in the power systems domain is well-established [18,36,66,67,83,92]. While their original application was often for power system market simulation [85], they have also been used in the context of power system stability control [71].…”
Section: Introduction: Resilience In Power System Coordination and Controlmentioning
confidence: 99%